The dynamic linkages of listed property companies in Pan-Asian countries [electronic resource] - Muhammad Yusaimi Abdul Hamid, 1992-, author; Muhammad Najib Razali, supervisor; Fakulti Geoinformasi dan Harta Tanah (2016)
Project Paper (Sarjana Muda Sains (Pengurusan Harta Tanah)) - Universiti Teknologi Malaysia, 2016